Perubahan Pola Kromatografi Lapis Tipis Ekstrak Daun dan Batang Teh (Camellia sinensis (L.) Kuntze) yang Menjadi Inang bagi 3 Benalu Berbeda - Irmanida Batubara; Lydia Octifani; Jarwadi Budi Hernowo (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2020)
Plants produce primary and secondary metabolite compounds depending on their growth conditions. The tea plant (Camellia sinensis (L.) Kuntze that hosts Loranthus produces different metabolites compared to those not hosting. This study aims to determine the change in the thin layer chromatography pattern (TLC) of leaf and stem tea extract that is the host 3 types of Loranthus tea namely Loranthus atropurpureus, Loranthus cochinchinensis, and Loranthus pentandrus. Leaf and stem tea extracts that host 3 types of Loranthus were separated using TLC with stationary phase of silica gel 60 F254 and the mobile phase of DCM: MeOH: n-hex (48:1:1). Separation results was detected using UV lamps 254 and 366 nm. The changes of the band's area of each extract were determined using software ImageJ. The results showed a change in TLC patterns. The declining band's area was found in bands detected at 366 nm for the host's stem and tea leaves. The increasing band's areawere found on bands detected at 254 nm especially on tea leaves that host. In conclusion, the change in TLC pattern can be used to determine the compounds that change due to tea plants to host and can be alternative utilization.